PWE-007 When to use hemospray? a single centre experience. (22nd June 2015) - Nasr, I; De Martino, S; Borrow, D-M; Dunn, JM
Abstract : Introduction: Hemospray is an inorganic nanopowder produced by Cook Medical and is licensed in Europe and Canada for the management of nonvariceal upper gastrointestinal bleed (NVUGIB). The powder adheres to liquid and forms a coagulum which concentrates clotting factors and stimulates the internal clotting cascade. There are numerous reports of successful haemostasis with hemospray, some reporting success rates of 85%. 1 However, the knowledge of which lesion is most suitable for hemospray use remains unclear. We report our experience at Guys and St Thomas' NHS trust to establish the lesions most likely to benefit from hemospray either as a primary intervention or an add-on strategy. Method: A retrospective review of endoscopic procedures that required hemospray was performed and the data was extracted from our endoscopy reporting system between December 2013 and February 2015 (14 months). We identified 32 patients who received hemospray, and excluded 2 where hemospray was applied blindly and the bleeding lesion was missed. The primary outcome was achieving primary haemostasis. Cases where primary haemostasis was not achieved or bleeding recurred requiring further endoscopic or radiological intervention were considered unsuccessful. Results: The 30 procedures were divided according to the procedure performed. Procedure induced bleeding: 9/30 (7 post Barrett's endoscopic mucosal resection (EMR), 1 post gastric polypectomy and 1 iatrogenic bleed post nasojejunal tube insertion). NVUGIB: 17/30. Enteroscopy small bowel bleed: 2/30. Colonoscopy: 2/30. Primary haemostasis was achieved in 80%, of which 10% required further endoscopic procedure or interventional radiological intervention (Table 1 ). The coagulum was not seen on second endoscopy. Conclusion: Hemospray provides good hemostasis for post procedure, in particular post EMR bleed, as a single agent or where coagulation alone failed. Bleeding from Forrest 1b, 2a and 2b responded well to hemospray as a second modality, or single modality when the lesion was inaccessible. Forrest 1a had a poor response to hemospray and all cases required further endotherapy or interventional radiology. Further evidence is required to establish the value of hemospray in colonic and variceal bleed. Disclosure of interest: None Declared. Reference: Smith et al . Hemospray application in nonvariceal upper gastrointestinal bleeding: results of the survey to Evaluate the application of hemospray in the luminal tract. J Clin Gastroenterol. 2014 Nov-Dec;48(10):e89-92